ХАБИТУАЛНИ МОРФОСИНТАКСИЧКИ СТРУКТУРИ (Filološke studije, 2019)
Habitualness is a complex aspect composed of two aspectual values: a subordinate moment and a dominant continuum, and its definition is as follows: X is such that (when/if S) P occurs. For example: Vo nedelite odime na Vodno: 'nie sme takvi što (koga/ako e nedela) se slučuva da otideme na Vodno' (On Sundays we go to Vodno: 'we are such that (when/if it is Sunday) we go to Vodno'.) The action designated by the habitual semanteme/structure represents the subordinate event P of habitualness (the moment), whereas the continuative dominant aspect is represented by the open possibility for the event to take place. The activator for the event to take place somewhere along the temporal line is the feasible condition S. At a formal level the aspectual category of habitualness in Macedonian is expressed by: 1) habitual semantemes, 2) habitual morphosyntactic structures and 3) habitual syntactic structures. At the morphosyntactic level the aspectual category of habitualness is expressed through verbal constructions composed of semantemes placed in an appropriate syntactic context, i.e. it is a combination of the aspectual value of the semanteme + its position (function) in the sentence. The habitual morphosyntactic structures in Macedonian are the following: 1. the ḱe-constructions; 2 the constructions with čini + imperative and 3. the da-constructions. The habitual ḱe-constructions (which are the habitual future tense, the habitual future-in-past tense and the habitual future perfect tense), and the constructions with čini + imperative are special morphosyntactic structures in the Macedonian language which are used to express a series of events reccurring in a determined order: Ḱe go pročitav vesnikot, ḱe pojaduvav i ḱe izlezev – 'I am such that (when/if S) it can occur for me to read the newspaper (P1), to have my breakfast (P2) and to get out (P3)' or: Toj čini – pojdi, dojdi i sè taka. The habitual future tense of perfective verbs in Macedonian is specialized for expressing a series of events in an open interval, and not in an assumed interval of habitualness, which results from the fact that the habitual perfective present does not exist in the modern Macedonian anymore, while it still exists in all other Slavic languages. The habitual da-constructions are complex verbal predicates composed of an introductory verb: znae, (mu) se slučuva, praktikuva or an introductory perifrastic structure: ima običaj, ima navika + the da-particle + perfective: pratikuva da zgotvi, ima običaj da dojde.